COMPETITIVENESS OF TOURISM AND HOTEL AND RESTAURANT ENTERPRISES: A SYSTEMATIC APPROACH TO MANAGEMENT (Development Service Industry Management, 2024)
The urgency of researching the competitiveness of tourism and hotel-restaurant enterprises is due to the need to increase their effective interaction to ensure quality service to tourists and increase the profitability of both industries. In modern conditions, tourists increasingly choose complex solutions that combine accommodation, food and entertainment, which stimulates interdependence and close cooperation between hotel and restaurant enterprises and tourist operators. In the conditions of increasing competition in the global market, enterprises must offer innovative products, provide a high level of service and convenience for customers, which makes partnerships between hotels, restaurants and travel agencies extremely important.The purpose of the study is to study the key factors that determine the ability of enterprises in the tourism and hotel and restaurant sectors to successfully compete in the modern service market.Therefore, modern realities dictate high requirements for the quality of services and an individual approach to each client. Tourists increasingly expect to receive not just accommodation and food, but unforgettable impressions and emotions. This encourages enterprises to constantly search for new solutions and implement innovations. An important aspect of competitiveness is the ability of enterprises to adapt to changes in the external environment. the competitiveness of tourism and hotel-restaurant enterprises is the ability of enterprises to successfully compete in the market, offering unique services and products that satisfy the needs of consumers better than the services of competitors. In the field of tourism and hospitality, competitiveness depends on many factors, including the quality of service, innovation, flexibility of business models, efficiency of resource management, as well as the ability to adapt to rapid changes in the market.To summarize, the competitiveness of tourism and hotel-restaurant enterprises is a multifaceted concept that covers a wide range of factors. To achieve success, enterprises need to constantly work on improving the quality of services, introducing innovations, adapting to market changes and effective interaction with partners.
Keywords: tourism; tourism entrepreneurship; integration; internally displaced persons; refugees